Stitches about the experience of a research-action center: beyond a methodological reflection - Alarcón, Tatiana Gutiérrez; Cruz, Andrea Neira (Universidade de São Paulo | Escola de Comunicações e Artes, 2018)
This article presents some questions that underlie the configuration of a research-action center within the framework of a Colombian University Educational Institution, from which an epistemological and methodological reflection is drawn about its work in permanent interaction with students, social organizations and community. It is exposed how this center contributes from its praxis, to construct critical or dissident perspectives that are in the way of overcoming the locus of enunciation that assumes a neutral and objective point of view unique to the western academy -in singular-, to build knowledge - in the plural - about our unjust and excluding realities deployed from the modern/colonial, capitalist, Eurocentric, patriarchal, racist civilizing project; In this sense, research-action is assumed as an unavoidable political and ethical field.